Spinal cord stimulation in treatment of patients with critical lower limb ischemia - A. V. Ashurkov; E. A. Levin; V. I. Murtazin; R. S. Kiselev; K. Yu. Orlov; A. L. Krivoshapkin; V. A. Shabalov (Патология кровообращения и кардиохирургия, 2017)
Critical limb ischemia (CLI) is a state of substantial reduction of blood flow in the extremities, mostly due to severe obstruction of the arteries. In lower limbs, it produces severe pain after even a short distance walk (intermittent claudication) and/or skin ulcers or sores. Surgical revascularization is a “golden standard” in CLI therapy, but it is contraindicated or not accessible for a large proportion of patients, while the medical prognosis is poor for conservative therapy. This situation stimulated the development of alternative approaches, including spinal cord stimulation (SCS) and various methods of “indirect” revascularization. In this paper, the authors give a short description of the latest approaches and a detailed review of the SCS method, while paying special attention to the studies that demonstrate not only a palliative effect of SCS (pain reduction), but also clinically significant changes in the indicators of lower limb muscles blood supply. CLI is characterized with a "vicious circle": pain causes reduced mobility and changes in the preferred limb position, which in turn lead to edema triggering an increase of ischemia and further elevation of pain. The clinical effects of SCS in CLI patients are related both with pain relief leading to a break of this vicious circle, and with the direct vasodilatory effects of the stimulation itself. There are several possible biological mechanisms of these actions, but most probably the therapeutic actions of SCS arise from their combination. Examination of different opinions about the appropriateness of spinal cord stimulation in patients with CLI, including those related to the economic efficiency of the method, leads to the conclusion that the evidence on these issues is currently insufficient. The reviewed data demonstrate the need for further development of the CLI treatment methods and high urgency of this problem. Received 6 April 2017. Accepted 23 April 2017. Funding: The study did not have sponsorship. Conflict of interest: The authors declare no conflict of interest.